2022
DOI: 10.1007/s11356-022-23876-y
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles induced testicular damage targeting NQO1 and APE1 dysregulation, apoptosis via Bax/Bcl-2 pathway, fibrosis via TGF-β/α-SMA upregulation in rats

Abstract: In medicine, silver nanoparticles (AgNPs) are employed often. They do, however, have negative impacts, particularly on the reproductive organs. This research aimed to assess AgNP impact on the testis and the possible intracellular mechanisms to induce testicular deteriorations in rats at various concentrations and different time intervals. Sprague Dawley rats (n = 40) were allocated into four equal groups: the control one, and three other groups injected intra-peritoneally with AgNP solution 0.25, 0.5, and 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…The increase NO level, MPO activity, and TNF‐α level observed in the AgNPs‐exposed rats in the current research suggests induction of inflammatory stress in the investigated tissues. Our current finding on cellular inflammatory response associated with AgNPs exposure is consistent with earlier studies 20,23 . Furthermore, activated cysteine‐aspartic protease known as caspase‐3 which executes apoptotic cell death following specific cleavage of cellular proteins was markedly increased following AgNPs treatment, thus indicating induction of apoptotic response in the hypothalamic, testicular and epididymal tissues.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The increase NO level, MPO activity, and TNF‐α level observed in the AgNPs‐exposed rats in the current research suggests induction of inflammatory stress in the investigated tissues. Our current finding on cellular inflammatory response associated with AgNPs exposure is consistent with earlier studies 20,23 . Furthermore, activated cysteine‐aspartic protease known as caspase‐3 which executes apoptotic cell death following specific cleavage of cellular proteins was markedly increased following AgNPs treatment, thus indicating induction of apoptotic response in the hypothalamic, testicular and epididymal tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Our current finding on cellular inflammatory response associated with AgNPs exposure is consistent with earlier studies. 20,23 Furthermore, activated cysteine-aspartic protease known as caspase-3 which executes apoptotic cell death following specific cleavage of cellular proteins was markedly increased following AgNPs treatment, thus indicating induction of apoptotic response in the hypothalamic, testicular and epididymal tissues. The marked abatement in the MPO activity, NO and TNF-α levels as well as caspase 3 activity in tissues of AgNPs-treated rats by exogenous administration of taurine indicates chemoprotection via anti-inflammatory and anti-apoptotic activities in the treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support the suggestions made by Al-Bairuty and Taha (2016) and De Jong et al (2019) that this type of exposure may be actually harmful. The cause of the animal's declining average body weight might be a biological alteration that influences the animal's appetite and feed intake, or it could be the disruption of several metabolic activities brought on by oral gavage (Assar et al, 2023). However, in recent studies performed by Ouni et al (2020) and Bugata et al (2019), it was found that daily oral administration of CuO NPs did not impact the feed intake and the weight of the body.…”
Section: Discussionmentioning
confidence: 99%